Book Reviews. (1st March 2015) - Edwards, Russell; Taylor, Melina
Abstract : Liquid Bread: Beer and Brewing in Cross-cultural Perspective Wulf Schiefenhövel and Helen Macbeth. (eds), New York: Berghahn (The Anthropology of Food and Nutrition Volume 7) 2011, ISBN: 978-1-78238-033-7, 264pp., Hb £75.00, U.S.$120.00, Pb £16.50, U.S.$26.00. Intimate Enemies: Violence and Reconciliation in Peru Kimberly Theidon, Philadelphia: University of Pennsylvania Press, 2013, ISBN: 978-0-8122-4450-2, 461pp. Hb $75.00, £49.00.